LIGHT ATHLETICS TO HIMSELF XOS FEATURES (INTERNATIONAL JOURNAL OF SCIENCE AND TECHNOLOGY, 2025)
This article focuses on exercises such as walking, running, jumping, and throwing in athletics. This article discusses theuniqueness of athletics.